2018
DOI: 10.1177/0030222818814052
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Reactions to the Loss of a Close Friend in an Extreme Terror Incident

Abstract: This article presents results from one of the first longitudinal studies exploring the effects of losing a close friend to traumatic death, focusing on complicated grief over time and how this is affected by avoidant behavior and rumination about the loss. The sample consists of 88 persons (76% women and 24% men, mean age = 21) who lost a close friend in the Utøya killings in Norway on July 22, 2011.Quantitative data were collected at three time-points; 18, 28, and 40 months postloss. Main findings are that be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…Grief rumination (repetitive thinking about the causes and consequences of the loss) was also higher in people with higher (vs. lower) CG symptom levels with a large effect size (Doering et al, 2018) and vice versa, high grief ruminators demonstrate higher CG symptom levels than low grief ruminators . Grief rumination and its subtypes generally show moderate to large positive associations with CG symptoms concurrently and longitudinally (Boelen, 2012;Boelen & van den Hout, 2008;Doering et al, 2018;Eisma et al, 2013;Johnsen et al, 2018;Pohlkamp et al, 2018;Tang et al, 2019;van der Houwen et al, 2010). In one study, grief rumination was related to CG symptoms, even when controlling for baseline symptoms (but this effect was marginally significant; Eisma et al, 2013).…”
Section: Ruminationmentioning
confidence: 98%
“…Grief rumination (repetitive thinking about the causes and consequences of the loss) was also higher in people with higher (vs. lower) CG symptom levels with a large effect size (Doering et al, 2018) and vice versa, high grief ruminators demonstrate higher CG symptom levels than low grief ruminators . Grief rumination and its subtypes generally show moderate to large positive associations with CG symptoms concurrently and longitudinally (Boelen, 2012;Boelen & van den Hout, 2008;Doering et al, 2018;Eisma et al, 2013;Johnsen et al, 2018;Pohlkamp et al, 2018;Tang et al, 2019;van der Houwen et al, 2010). In one study, grief rumination was related to CG symptoms, even when controlling for baseline symptoms (but this effect was marginally significant; Eisma et al, 2013).…”
Section: Ruminationmentioning
confidence: 98%
“…This social support may interact with additional social factors such as positive media coverage, greater legal victims' rights, greater financial compensation, sensitive and positive experiences with police, legal authorities, medical services, social support groups, and so forth-which may all moderate terror-related HB pathogeny. Murphy, Johnson, Wu, et al (2003), Pfeffer et al (2007) 2020), Keesee et al (2008), King (2004) Unmet expectations for short-term grief Armour (2002Armour ( , 2003, Laurie and Neimeyer (2008) Social non-approval of grief over the victim Johnsen and Dyregrov (2016), Pavon and Basile (2022) Unmet social expectations on grief coping strategies Sharpe and Boyas (2011), Sharpe et al (2014) Unmet gendered expectations on grief Kenney (2003) Bereaved person's beliefs in victim's afterlife Giannopoulou et al (2018), Park and Benore (2004) Victim and bereaved person belonging to ethnic, racial, or socially marginalized and stigmatized group Burke et al (2010), Laurie and Neimeyer (2008), Pavon and Basile (2022), Sharpe (2008), Sharpe et al (2014), Stretesky et al (2010) HB = homicide bereavement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these observations and extrapolations on intrasocietal diversity in HB risk factors and given scholars' attestation to the crucial link between HB risk factors and macro sociocultural norms and expectations (Armour, 2002(Armour, , 2003Johnsen & Dyregrov, 2016;Laurie & Neimeyer, 2008;Pavon & Basile, 2022;Sharpe & Boyas, 2011;Sharpe et al, 2014), reports on intersocietal diversity across societies and cultures should come as no surprise. For example, contrary to findings in Western societies reporting greater pathogenic effects among grief related to homicide, Ogata et al (2011) noted that in Japan, HB may occur irrespective of the manner of death, because any unusual loss of a Japanese family member can remind surviving members of the traumatic event (p. 532).…”
Section: Table 2 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Closeness in a relationship includes features like trust, intimacy, and mutual support [ 15 ]. In the total sample of our study, the mean of the self-reported evaluation of the closeness of the relationship (ranging from 1 to 10) was 8.89 [ 42 ]. Complicated grief and somatic symptoms can be related to the quality of the relationship (depth/conflict) with the deceased friend, and those who reported greater depth in their relationship were more likely to have complicated grief [ 40 ], and emotional closeness to the deceased can cause more intense grief reactions [ 25 , 43 ]].…”
Section: Discussionmentioning
confidence: 99%